A Literary Appreciation of the Book of Judges - Lilley, J. P. U. (Tyndale bulletin, 1967)
Fresh appraisal of Judges as a literary work, starting from the assumptions of authorship rather than of redaction, could lead to a more satisfying interpretation of the book.